Level of Understanding of Sports Injury Management With T.O.T.A.P.S METHOD Among Members of the Student Activity Unit Futsal at Universitas Mercu Buana Yogyakarta - Wilson Sotar Dodo Simamora; Yulius Agung Saptro (Pusdikra-Publishing.com, 2024)
This study aims to determine the level of understanding of handling sports injuries using the T.O.T.A.P.S method among members of the Futsal Student Activity Unit (UKM) at Mercu Buana University, Yogyakarta. This type of research uses qualitative descriptive research conducted using a survey method distributed via Google Form. There were 51 members of UKM Futsal UMBY who were the samples in this research. To calculate the percentage included in the category in each aspect, the formula is used, namely: P = F/N x 100%. The results of this study concluded (1) understanding of the factors that cause sports injuries in the